The preponderance of nonsynonymous A-to-I RNA editing in coleoids is nonadaptive - Daohan Jiang (Nature Portfolio, 2019)
The neural tissues of coleoids have a greater fraction of nonsynonymous sites than synonymous sites subject to high levels of A-to-I RNA editing, a pattern thought to indicate widespread adaptive editing. Here the authors propose and provide evidence for an alternative, nonadaptive explanation.